Entwined lives: twins and what they tell us about human behavior - Segal, Nancy L. (A Dutton Book, 1999)
"Bringing together the latest, cutting-edge research, with illustrative case histories of twins and their families, preeminent twin researcher Dr. Nancy L. Segal explores ways in which twins enhance our knowledge of human behavioral and physical development." "How twins hold a mirror up to ourselves is reflected in real-life stories like those of Jim Lewis and Jim Springer, identical twin brothers separated at birth and reunited at age thirty-nine. In addition to having the same jobs, cars, hobbies, and health histories, each discovered in the other a long-lost best friend, in-laws, and nieces and nephews. Bernard J. Shapiro, Ph.D., and Harold T. Shapiro, Ph.D., the only known twins to share the distinction of becoming presidents of leading universities, were uncertain if they were identical or fraternal twins until the age of sixty-two. These, along with many other case histories documented in this fascinating book, go a long way toward helping us solve our behavioral riddles."--BOOK JACKET